Expression of manganese superoxide dismutase in rat blood, heart and brain during induced systemic hypoxia (Medical Journal of Indonesia, 2011)
Background: Hypoxia results in an increased generation of ROS. Until now, little is known about the role of MnSOD - a major endogenous antioxidant enzyme - on the cell adaptation response against hypoxia. The aim of this study was to determine the MnSOD mRNA expression and levels of specific activity in blood, heart and brain of rats during induced systemic hypoxia. Methods: Twenty-five male Sprague Dawley rats were subjected to systemic hypoxia in an hypoxic chamber (at 8-10% O2) for 0, 1, 7, 14 and 21 days, respectively. The mRNA relative expression of MnSOD was analyzed using Real Time RT-PCR. MnSOD specific activity was determined using xanthine oxidase inhibition assay. Results: The MnSOD mRNA relative expression in rat blood and heart was decreased during early induced systemic hypoxia (day 1) and increased as hypoxia continued, whereas the mRNA expression in brain was increased since day 1 and reached its maximum level at day 7. The result of MnSOD specific activity during early systemic hypoxia was similar to the mRNA expression. Under very late hypoxic condition (day 21), MnSOD specific activity in blood, heart and brain was significantly decreased. We demonstrate a positive correlation between MnSOD mRNA expression and specific activity in these 3 tissues during day 0-14 of induced systemic hypoxia. Furthermore, mRNA expression and specific activity levels in heart strongly correlate with those in blood. Conclusion: The MnSOD expression at early and late phases of induced systemic hypoxia is distinctly regulated. The MnSOD expression in brain differs from that in blood and heart revealing that brain tissue canÂ possibly survive better from induced systemic hypoxia than heart and blood. The determination of MnSOD expression in blood can be used to describe its expression in heart under systemic hypoxic condition. (Med J Indones 2011; 20:27-33) Keywords: MnSOD, mRNA expression, ROS, specific activity, systemic hypoxia